Pengaruh Ekonomi Makro dan Mikro terhadap Non Performing Financing pada Bank Umum Syariah di Indonesia - Retnosari, Suci Ardiana; Farida, Farida (Borobudur Accounting Review, 2021)
This study aims to examine and analyze the effect of inflation, Indonesian Sharia securities, capital adequacy, profitability, third party funds, efficiency and bank size on non-performing financing in Islamic commercial banks registered with the Financial Services Authority (OJK) 2015-2019. The data in this study are secondary data. The sample used in this study is a Sharia Commercial Bank registered with the Financial Services Authority from 2015 to 2019. The total population of this study is 14 Islamic Commercial Banks. Based on the sampling method with purposive sampling with a research period of 5 years from 2015 - 2019, a total of 11 samples were obtained. Hypothesis testing was carried out using multiple linear regression analysis. The results showed that inflation, SBIS, Capital Adequacy, Third Party Funds, and efficiency had no effect on Non-Performing Financing, while Profitability and Bank Size had a significant negative effect on Non-Performing Financing.